California Democratic Council Convention at Fresno Hilton Hotel - Watkins, Howard::::::::: (1979)
US Senator Alan Cranston speaking; head table: CDC President Wallace Albertson, Cranston, ?, Rose Ann Vuich, ?, Tom Hayden